2004
DOI: 10.1109/jlt.2004.829187
|View full text |Cite
|
Sign up to set email alerts
|

Flat-Gain Fiber Raman Amplifiers Using Equally Spaced Pumps

Abstract: Abstract-This paper analyzes the gain flatness of multiwavelength pumped fiber Raman amplifiers using equally spaced pumps with both a fixed and an optimized central pump wavelength. The signal gain ripple using equally spaced pumps is compared with the case in which the pump wavelengths are allowed to vary for two, four, and eight pumps with 20-, 40-, and 80-nm signal bandwidths. The paper shows that using an optimized central pump wavelength with equal pump spacing simplifies system design, while the gain ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…The amplification bandwidth is 38 nm, which, to the best of the authors' knowledge, is the widest amplification bandwidth ever reported from the dual-wavelength pumping scheme. This also corresponds well to the suggested bandwidth of 40 nm based on the simulation result using dual-pump wavelength in [8]. Based on the experimental results, gain saturation is very minimal for the distributed Raman amplifier, as also reported in [13].…”
Section: Resultssupporting
confidence: 88%
“…The amplification bandwidth is 38 nm, which, to the best of the authors' knowledge, is the widest amplification bandwidth ever reported from the dual-wavelength pumping scheme. This also corresponds well to the suggested bandwidth of 40 nm based on the simulation result using dual-pump wavelength in [8]. Based on the experimental results, gain saturation is very minimal for the distributed Raman amplifier, as also reported in [13].…”
Section: Resultssupporting
confidence: 88%
“…The analysis of gain flatness of Raman fiber amplifier is reported in Ref. [16] for equally spaced multiwavelength pump power and a new method is proposed using modified shooting algorithm to design a small gain ripple and flat gain spectrum Raman fiber amplifier [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although various numerical optimisation methods have already been proposed (Yan et al 2001, Perlin and Winful 2002, Muktoyuk et al 2004, Liu and Li 2004, Hu et al 2004) each with their specific advantages and limitations, development of new approaches is of interest to address the variety of applications and practical boundary conditions and constraints.…”
Section: Introductionmentioning
confidence: 99%